KONSEP UANG MENURUT AL-GHAZALÎ - Jalaluddin Jalaluddin (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2014)
Al-Ghazalî is known as an intellectual figure who mastered various sciences. Almost all the religious aspects he studied in depth, including the issue of money. The learning process he did until he died. In the field of Islamic knowledge, there are proof which show many scholars who admitted to his mastered knowledge with tremendous enthusiasm. This paper is presented to describe the thought of al-Ghazalî, such as the understanding of money, the concept of money, the kind of money, the function of money, and the contribution of money to the Islamic economic system. The sources of data in this paper takes a lot from the phenomenal book of al-Ghazalî, namely Ihya al-‘Ulûmuddîn, as well as from other books related to this paper.